2017
DOI: 10.20964/2017.12.57
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oxidation of Ethylene Glycol on PtSn/C for Application in Alkaline Fuel Cell

Abstract: PtSn/C electrocatalysts with different molar ratios were synthesized by borohidrate process for glycol ethylene oxidation. All electrocatalysts were, also, characterized by X-ray diffraction (XRD), transmission electronic microscopy (TEM), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIRS), energy dispersive X-ray (EDX), while the electrochemical activities of those materials were evaluated by cyclic voltammetry, chronoamperometry and polarization curves in Direct Ethylene Glycol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…e D2 interband, also called D * has been attributed sp 2 -sp 3 bond in carbon lattice [17], and when its value decreases it can be assumed that the crystallinity in the nanodomains increases, therefore, AB7-f has a more crystalline nanodomain structure than AB7. is occurs because microwave heating promotes the release of carbon and oxygen from the carbon material, generating small conjugated graphitic domains, which improves crystallinity [18]. In addition, D3 interband (≈1500 cm −1 ) can be related to small functional groups and SP2-bonded forms, and it has been reported that when D3 interband intensity decrease the crystallinity increase [19], which is in good agreement with our results.…”
Section: Resultssupporting
confidence: 91%
“…e D2 interband, also called D * has been attributed sp 2 -sp 3 bond in carbon lattice [17], and when its value decreases it can be assumed that the crystallinity in the nanodomains increases, therefore, AB7-f has a more crystalline nanodomain structure than AB7. is occurs because microwave heating promotes the release of carbon and oxygen from the carbon material, generating small conjugated graphitic domains, which improves crystallinity [18]. In addition, D3 interband (≈1500 cm −1 ) can be related to small functional groups and SP2-bonded forms, and it has been reported that when D3 interband intensity decrease the crystallinity increase [19], which is in good agreement with our results.…”
Section: Resultssupporting
confidence: 91%
“…However, in the case of activated carbon, heptadecane was the main product at 100% conversion, with 70.1% selectivity. This can be explained by the fact that due to the weak affinity of carbon, Pt–Sn bimetals do not tend to form an alloy on carbon . These results indicated that SiO 2 and Al 2 O 3 are optimal supports for Pt–Sn bimetallic catalysts to deoxygenate stearic acid to olefins.…”
Section: Resultsmentioning
confidence: 98%
“…This can be explained by the fact that due to the weak affinity of carbon, Pt−Sn bimetals do not tend to form an alloy on carbon. 14 These results indicated that SiO 2 and Al 2 O 3 are optimal supports for Pt−Sn bimetallic catalysts to deoxygenate stearic acid to olefins. To avoid the influence of the acidity of Al 2 O 3 in the reaction, we selected neutral SiO 2 as the support for further studies.…”
Section: Resultsmentioning
confidence: 99%